Implementasi Fungsi Dewan Perwakilan Rakyat Aceh Dalam Penyusunan Anggaran - Syukriah Syukriah; Putri Lisdianti (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Article 22 of Law Number 11 of 2006 on Government of Aceh states that "The Aceh House of Representative (DPRA) and the Regency House of Representative (DPRK) have legislative, budgetary and supervisory functions". Then, the third part of article 25 concerning the rights, obligations and code of ethics in paragraphs (1) letters g and h states that the DPRA/DPRK compiles a budget plan in accordance with the functions, duties and authority of the DPRA/DPRK as part of the Aceh Revenue and Expenditure Budget and Regency/municipality Revenue and Expenditure Budgets using a price standard agreed by the Governor with the DPRA/DPRK. However, in reality the DPRA did not carry out its functions properly, resulting in delays in APBA ratification which could result in a number of executive agendas that were dependent on Budget approval that could worsen the economic conditions of the people of Aceh, which were stipulated by a Governor Regulation.